Biomedical packages: Adjusting drugs, bodies, and environment in a phase III clinical trial (Medicine Anthropology Theory, 2020)
Clinical trials are a fundamental stage in a drug’s biography for they provide the standard by which a molecule’s therapeutic status is determined. Through this process of experimentation, a pharmaceutical substance acquires a new competence – that of treating or preventing disease. This article examines experimentation in drug production, and shows how this complex apparatus not only transforms the status of the molecule but also produces new understandings of and expectations for how people should act. Drawing upon observation of a trial of prophylactic prevention of mother-to-child transmission of HIV, in Ouagadougou, Burkina Faso, I show that the production of this biomedical technology – the therapeutic drug – is coupled with the production of its users. In so doing, I challenge the conception of drugs as bounded objects and instead offer the concept of ‘biomedical package’, which highlights the social relations that characterise it.